Isokinetic and isometric muscle function of the knee extensors and flexors during simulated soccer activity: Effect of exercise and dehydration - Ali, A.; Williams, C. (Journal of Sports Sciences, 2013)
This study investigated the influence of dehydration during soccer-type intermittent exercise on isokinetic and isometric muscle function. Eight soccer players performed two 90-min high-intensity intermittent shuttle-running trials without (NF) or with (FL) fluid ingestion (5 ml/kg before and 2 ml/kg every 15 min). Isokinetic and isometric strength and muscular power of knee flexors and knee extensors were measured pre-exercise, at half-time and post-exercise using isokinetic dynamometry. Sprint performance was monitored throughout the simulated-soccer exercise. Isokinetic knee strength was reduced at faster (3.13 rad/s; P = 0.009) but not slower (1.05 rad/s; P = 0.063) contraction speeds with exercise; however, there was no difference between FL and NF. Peak isometric strength of the knee extensors (P = 0.002) but not the knee flexors (P = 0.065) was significantly reduced with exercise with no difference between FL and NF. Average muscular power was reduced over time at both 1.05 rad/s (P = 0.01) and 3.14 rad/s (P = 0.033) but was not different between FL and NF. Mean 15-m sprint time increased with duration of exercise (P = 0.005) but was not different between FL and NF. In summary, fluid ingestion during 90 min of soccer-type exercise was unable to offset the reduction in isokinetic and isometric strength and muscular power of the knee extensors and flexors.